A Framework for city leadership in multilevel governance settings: the comparative contexts of Italy and the UK. Issue 1 (1st January 2016) - Budd, Leslie; Sancino, Alessandro
Abstract : This paper discusses the role of city leadership in the current multilevel governance settings and provides a conceptual framework for understanding the main elements of city leadership. Forms of political, managerial and civic leadership have been distinguished within city leadership and the main actors, structures, processes and followership patterns are examined using Italy and the UK as starting points of comparison. This comparative framework sheds a light on some common and different features in the city leadership patterns in Italy and the UK, such as the cross-cutting and multilayered administrative context for public service delivery; the common trend towards strengthening the executive side of political leadership rather than the representative one; the growing relevance of forms of civic leadership as a trigger for creating public and social value and for enhancing the resilience of the territories. Main differences deal instead with the role of central government in defining the role of city leaders, where Italy seems to experience a return towards greater centralization and controls, and the UK is experiencing an opposite trend towards the empowerment of local communities. Finally, the paper sets out some future directions for the research agenda on city leadership we are seeking to pursue.